Phylogenetic analysis of ionotropic L-glutamate receptor genes in the Bilateria, with special notes on Aplysia californica. Issue 1 (December 2017) - Greer, Justin; Khuri, Sawsan; Fieber, Lynne
Abstract Background The neurotransmitter L-Glutamate (L-Glu) acting at ionotropic L-Glu receptors (iGluR) conveys fast excitatory signal transmission in the nervous systems of all animals. iGluR-dependent neurotransmission is a key component of the synaptic plasticity that underlies learning and memory. During learning, two subtypes of iGluR, α-Amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptors (AMPAR) and N-methyl-D-aspartate receptors (NMDAR), are dynamically regulated postsynaptically in vertebrates. Invertebrate organisms such asAplysia californica (Aplysia ) are well-studied models for iGluR-mediated function, yet no studies to date have analyzed the evolutionary relationships between iGluR genes in these species and those in vertebrates, to identify genes that may mediate plasticity. We conducted a thorough phylogenetic analysis spanning Bilateria to elucidate these relationships. The expression status of iGluR genes in theAplysia nervous system was also examined. Results Our analysis shows that ancestral genes for both NMDAR and AMPAR subtypes were present in the common bilaterian ancestor. NMDAR genes show very high conservation in motifs responsible for forming the conductance pore of the ion channel. The number of NMDAR subunits is greater in vertebrates due to an increased number of splice variants and an increased number of genes, likely due to gene duplication events. AMPAR subunits form an orthologous group, and there is high variability in the number of AMPAR genes in each species due to extensive taxon specific gene gain and loss. qPCR results show that all 12Aplysia iGluR subunits are expressed in all nervous system ganglia. Conclusions Orthologous NMDAR subunits in all species studied suggests conserved function across Bilateria, and potentially a conserved mechanism of neuroplasticity and learning. Vertebrates display an increased number of NMDAR genes and splice variants, which may play a role in their greater diversity of physiological responses. Extensive gene gain and loss of AMPAR genes may result in different physiological properties that are taxon specific. Our results suggest a significant role for L-Glu mediated responses throughout theAplysia nervous system, consistent with L-Glu's role as the primary excitatory neurotransmitter.